THE RETURN TO KEYNESIANISM IN OVERCOMING CYCLICAL FLUCTUATIONS? - Praščević, Aleksandra (Economic Annals, 2008)
The problems faced by the American economy in the second half of 2007 , which intensified in 2008 , have once again asked economic science, and even more so economic policy, questions relating to business cycles – the reasons for cyclical fluctuations, the character of business cycles and, naturally, economic policy measures that can be implemented to alleviate and overcome an economic recession. Since the 1970s, business cycle theories have been intensively developed – ranging from monetary theories, developed within monetarism and the first phase of New Classical Macroeconomics, to the real business cycle theory of New Classical Macroeconomics. Consequently, the triggers for the beginning of a cycle can be monetary (monetary theories) or real in the form of technological shocks (real business cycles). In essence economic policy conducted since the 1970s, has rejected the Keynesian explanations of the functioning of the economic system, and thus the policy of aggregate demand management. However, the measures that are now being implemented in the USA point to a return to Keynesianism. This refers, above all, to attempts to compensate for the inefficiency of monetary policy with fiscal expansion. All three psychological propensities (propensity to consume, propensity to invest and liquidity preference) in Keynes's theory and applied in Keynesian economic policy, are still the significant determinants of monetary and fiscal policies. The return to Keynesianism points to the depth of the crisis faced by the USA , but also confirms the vitality of Keynesian economics and affirms the view that – although Keynes wished to present his theory as being “general” – it is actually the theory of economic depression.